Juvenile Spondyloarthritis: What More Do We Know About HLA-B27, Enthesitis, and New Bone Formation? - Tay, Shi Huan; Yeo, Joo Guan; Leong, Jing Yao; Albani, Salvatore; Arkachaisri, Thaschawee (Frontiers in Medicine, 2021)
Juvenile spondyloarthritis (JSpA) refers to a diverse spectrum of immune-mediated inflammatory arthritides whose onset occurs in late childhood and adolescence. Like its adult counterpart, JSpA is typified by a strong association with human leukocyte antigen-B27 (HLA-B27) and potential axial involvement, while lacking rheumatoid factor (RF) and distinguishing autoantibodies. A characteristic manifestation of JSpA is enthesitis (inflammation of insertion sites of tendons, ligaments, joint capsules or fascia to bone), which is commonly accompanied by bone resorption and new bone formation at affected sites. In this Review, advances in the role of HLA-B27, enthesitis and its associated osteoproliferation in JSpA pathophysiology and treatment options will be discussed. A deeper appreciation of how these elements contribute to the JSpA disease mechanism will better inform diagnosis, prognosis and therapy, which in turn translates to an improved quality of life for patients.